Factors Affecting Early Marriage: A Literature Review - Nuriati Sarlota Auprai; Rosdiana Tandiola; Isak J.H. Tukayo (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: One of the current phenomena is early marriage. Given the current situation in Indonesian society, early marriage has become a familiar phenomenon and is considered normal by the general public. In fact, it has occurred in many regions in Indonesia. Although early marriage has a significant impact on life, it continues to be a problem in society. This can be caused by various factors. Purpose: to identify the causal factors associated with early teenage marriage. Methods: This article was written using a literature review method through previous research articles found in the Google Scholar database. Articles were selected based on the criteria of articles published between 2020 and 2024. The literature review analysis was conducted by comparing the research methods, processing, and results obtained from each article. Results: Factors that can influence early marriage include education, knowledge, sexual behavior, premarital pregnancy and promiscuity, socioeconomic factors, income, employment status and wealth index, parenting and religious education, family perceptions and culture, demographics and type of residence, parental factors and matchmaking, peer influence and family support, mass media and access to information, debt and self-determination. Conclusion: Early marriage can be caused by various factors that have been proven to be closely related. Therefore, preventive efforts are needed through education and economic development in the communiti, monitoring adolescent relationships, and improving education/skills for adolescents.